IMPROVING AESTHETIC TRAINING OF 5TH GRADERS ON THE BASIS OF NATIONAL EMBROIDERY (American Journal of Research in Humanities and Social Sciences, 2023)
This thesisalso discusses the methodology of aesthetic training based on teaching national embroidery samples to 5th graders in teaching, integrating its history and some aspects.